Macrophage suppression following phagocytosis of apoptotic neutrophils is mediated by the S100A9 calcium-binding protein - De Lorenzo, B. H. P.; Godoy, L. C.; Novaes e Brito, R. R.; Pagano, R. L.; Amorim-Dias, M. A.; Grosso, D. M.; Lopes, J. D.; Mariano, M. [UNESP] (Elsevier Gmbh, Urban & Fischer Verlag, 2010)
The clearance of apoptotic cells by phagocytes is a fundamental process during tissue remodeling and resolution of inflammation. In turn, the phagocytosis of apoptotic cells generates signals that suppress pro-inflammatory activation of macrophages. These events occur during the resolution phase of inflammation and therefore the malfunctioning of this process may lead to inflammation-related tissue damage. Here, we demonstrate that the calcium-binding protein S100A9, normally abundant in the cytoplasm of neutrophils and also released by apoptotic neutrophils, is involved in the suppression of macrophages after the uptake of apoptotic neutrophils. Both, spontaneous and induced production of inflammatory species (nitric oxide, hydrogen peroxide and TNF-alpha) as well as the phagocytic activity were inhibited when macrophages were in presence of apoptotic neutrophils, conditioned medium from neutrophil cultures or a peptide corresponding to the C-terminal region of S100A9 protein. on the other hand, macrophages kept in the conditioned medium of neutrophils that was previously depleted of S100A9 were shown to resume the activated status. Finally, we demonstrate that the calcium-binding property of S100A9 might play a role in the suppression process, since the stimulation of intracellular calcium release with ionomycin significantly reversed the effects of the uptake of apoptotic neutrophils in macrophages. In conclusion, we propose that S100A9 is a novel component of the regulatory mechanisms of inflammation, acting side-by-side with other suppressor factors generated upon ingestion of apoptotic cells. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Apoptotic neutrophils; Calcium-binding proteins; Inflammation; Macrophage suppression; Resistance to infection; S100A9